KEBERSYUKURAN DAN OPTIMISME TERHADAP KESEJAHTERAAN PSIKOLOGIS MAHASISWA YANG BEKERJA - Firmansyah, Ferry; Prestiana, Novita Dian Iva; Setiawan, Rony (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2024)
This research was conducted to determine the relationshipbetween romantic love type and subjective well-being in youngadults in Bekasi City. This is based on the large number ofdating relationships carried out by young adults with differentbeliefs. The existence of interfaith relationships can onlyincrease the number of interfaith marriages in Indonesia.Subjective well-being is an important component of life.Romantic relationships become a domain of life in a person'ssubjective well-being. Therefore, romantic love becomes asubjective well-being factor for a person. The instrument formeasuring romantic love used in this research is a scalemodified by Stenberg and developed by Rosita Aryani. Forsubjective well-being, two measuring instruments are used,namely the SWLS (Satifaction With Life Scale) which wasadapted by Diener (1985) and the SPANE (Scale of Positiveand Negative Experience) measuring instrument which wasadapted by Diener (2009). The participants in this researchwere 59 young adults who had relationships with differentreligions in Bekasi City. Through the Spearman Rank analysistechnique, it is known that there is a significant relationship between the variabel type of romantic love and subjective well-being (correlation coefficient of (0.334) and significance value ᑭ= 0.010 where ᑭ < 0.05) and through the Multiple LinearRegression analysis technique it can be interpreted even thoughthe effect is not strong, but there is a significant contributionfrom the type of romantic love to the level of subjectivesatisfaction (the coefficient of determination (R Square) of0.112 indicates that it is around 11.2%).